Electrochemical advanced oxidation processes for sanitary landfill leachate remediation: Evaluation of operational variables - Francisca C. Moreira (2016)
The effect of various parameters on the performance of electrochemical advanced oxidation processes (EAOPs) like electro-Fenton (EF), photoelectro-Fenton (PEF) and solar PEF (SPEF) was assessed for the treatment of a sanitary landfill leachate previously subjected to biological and coagulation processes. The tested operational variables included: (i) anode material (boron-doped diamond (BDD) and Pt), (ii) initial total dissolved iron concentration (20-80 mg L-1), (iii) pH (2.8-4.0), (iv) initial addition of 1:3 Fe(III)-to-oxalate molar ratio at various pH values (2.8-5.0), (v) temperature (15-40 degrees C) and (vi) radiation source (UVA, UVA-Vis and UVC lamps and natural sunlight). The BDD anode showed high superiority over the Pt one for EF, PEF with UVA light (PEF-UVA) and SPEF processes, thereby advising an important role of the physisorbed hydroxyl radicals ((OH)-O-center dot) at the anode surface on landfill leachate oxidation even under the potent solar radiation. An initial total dissolved iron content of 60 mg L-1 was chosen as the best dose for the PEF-UVA process with the BDD anode (PEF-BDD-UVA). While PEF-BDD-UVA without external addition of oxalic acid yielded the best results at pH 2.8, the initial addition of 1:3 Fe(III)-to-oxalate molar ratio allowed operating at pH 3.5 with even higher efficiency and at pH 4.0 with only slightly lower efficiency. Effluent temperatures from 20 to 40 degrees C led to similar mineralization rates for the PEF-BDD-UVA technique. The use of UVA and UVC lamps and natural sunlight as radiation sources in PEF-BDD and SPEF-BDD systems led to similar mineralization profiles as a function of time. The UVA-Vis lamp induced lower effluent mineralization mainly for longer reaction times.